DAKWAH SUFISTIK HAMZAH FANSURI (Kajian Substantif terhadap Syair “Perahu”) - Zakaria Zakaria (Universitas Islam Negeri Ar-Raniry, 2013)
Hamzah Fansuri is an archipelago Sufism figure who wrote many works. These works are in the field of mind and his message of Sufism. Perahu poem is one of his monumnetal works. It contains the teachings of philosophical Sufism. However, the concept and substance of the poem is not widely known in the public. Hamzah Fansuri in perahu poem used many symbols. The dakwa symbols used in the perahu poem is